On the temporal stability of self-determined work motivation profiles: a latent transition analysis - Fernet, C.; Litalien, D.; Morin, A.J.S.; Austin, S.; Gagné, Marylène; Lavoie-Tremblay, M.; Forest, J. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
© 2019 Informa UK Limited, trading as Taylor & Francis.